Implementation Of Public Services Policy In Traditional Market Arrangement In Siborong-borong Market, North Tapanuli Regency - Pryda R. Hutasoit (IHSA Institute, 2021)
Traditional markets are places where community activities take place to help survival and the economy. The existence of the buying and selling process in Traditional Markets certainly has a negative side and a positive side as we can see that many traditional markets in Indonesia seem slum, chaotic, dirty, smelly and become a source of traffic jams. The problems that occur in the Siborongborong Traditional Market are not much different from the conditions of the Traditional Market in general. Therefore, researchers are interested in conducting research with the title Implementation of Public Service Policies in Structuring Traditional Markets at Siborongborong Market, North Tapanuli Regency. The research method used in this study uses a descriptive qualitative approach, which explains the phenomenon in depth through data collection. Data collection techniques are interviews, observations and documents related to research. This study uses the indicators proposed by Van Meter and Van Horn covering basic measures and policy objectives (policy objectives), policy sources (resources), inter-organizational communication and implementation activities (communication), characteristics of implementing agencies, social, economic and political conditions, disposition (attitude of implementers). From this research, it can be concluded that the implementation of public service policies in the arrangement of the Siborongborong traditional market has not met the standard of policy targets. The Department of Industry and Trade and UPT Pasar have tried to work in accordance with the existing main tasks and functions, but the problem is the availability of reliable staff. Communication of the Department of Industry and Trade has not been realized properly because the community and implementing agents cannot unite perceptions, while the economic condition cannot be said to be good because perhaps the factor of traders selling adjacent (side) this policy cannot be implemented properly because the community accepts the policy but does not implement the rules that have been made.